Communication satisfaction level among instructional leaders at an Integrated Islamic Private School / Sazimalily Mat Don - Mat Don, Sazimalily (2014)
The main purpose of this study was to examine the communication satisfaction level among Instructional Leaders (IL) at an Integrated Islamic Private School (IIPS). The instrument employed was the Communication Satisfaction Questionnaire (CSQ) developed by Downs and Hazen (1977). The data for this study was collected from 33 respondents which comprised 12 males and 21 females. At the same time there the 33 respondents comprised 18 novice and 15 experienced teachers. Four teachers were randomly selected for interview session. Descriptive data revealed that majority of the respondents were satisfied with the following dimensions of communication: i.e. supervision communication, organizational integration, horizontal communication and subordinate communication. They were moderately satisfied with communication climate, personal feedback, media quality and corporate information. The t-test analysis also revealed that there was no significant difference between male and female teachers in their communication satisfaction level. Furthermore, there was also no significant difference between novice and experienced teachers in their communication. Nevertheless, the main challenges faced by respondents with regards to communication are miscommunication, unclear information, lack of personal feedback, nature of the environment and the fact that employees are not open to each other. This study recommends that school leaders must take steps to ensure clear and open channels of communication are maintained at all times to build effective learning organisations.